Identification of a New High Geraniol Rich Variety "Jor Lab L-15" of Lemongrass [Cymbopogon khasianus (Hack) Stapf (ex Bor)]. Issue 4 (4th July 2019) - Lal, Mohan; Borah, Angana; Pandey, Sudin Kumar
Abstract: Cymbopogon species, which belongs to the family Poaceae, is an important genus of medicinal and aromatic plants. The essential oil of the species of genus is rich in various valuable chemical compounds, which are useful for industrial and commercial purposes. In this present study, a total of 425 germplasm of Cymbopogon species were collected from different regions of India, and was analyzed for its agronomical, essential oil yield and quality data, for two year 2014-15 and 2015-16.Extraction of essential oil was done using hydro-distillation and the constituents were identified using GC/MS analysis. On the basis of two consecutive year data, a geraniol rich line was identified and the results were confirmed by planting as multi-location trial, along with the standard check during the year 2016-17 and 2017-18. The average essential oil yield of the newly developed variety in the five different locations was 0.54 % and average geranial content of the multi-location trial was 83 %; which is much higher as compared to the check variety that showed essential oil yield of 0.40 % and geraniol content of 46.8 %. This selected germplasm also showed better agronomical traits in comparison to the check variety. This new identified line was named as "Jor Lab L-15" and is suitable for commercial cultivation.